Proteomic Analysis of Potential Targets for Non-Response to Infliximab in Patients With Ulcerative Colitis - Liu, Lu; Pu, Dan; Wang, Dandan; Zhang, Muhan; Zhou, Chuan; Zhang, Zhe; Feng, Baisui (Frontiers in Pharmacology, 2022)
Background: Infliximab (IFX) is a potent therapeutic agent for the treatment of conventional refractory ulcerative colitis (UC). However, the high non-response rate of IFX brings difficulties to clinical applications. In the context of proteomics research, our study of differentially expressed proteins (DEPs) essential for non-response to IFX in UC patients, and provide powerful insights into underlying drug resistance mechanisms. Methods: Total of 12 UC patients were divided into responders to IFX (UCinfG), non-responders to IFX (UCinfL), severe UC (UCsevere) without IFX treatment history and mild UC (UCmild) without IFX treatment history. Subsequently, DEPs were identified from intestinal biopsy tissue between responders and non-responders to IFX by Label-free proteomic quantitative approach, and the general principle of functional protein screening was followed to deduce the potential drug targets and predictors for non-response to IFX in UC patients. Meanwhile, these targets excluded DEPs caused by severity of inflammation for the first time. The differential expressions of candidate protein targets were validated at the gene sequence level using GEO2R analysis of the GEO database and qRT-PCR in some independent cohorts. Results: 257 DEPs were screened out by mass spectrometry between UCinfG and UCinfL groups, excluding 22 DEPs caused by the severity of inflammation, and compared and verified at the gene sequence level in the Gene Expression Omnibus (GEO) database. Finally, 5 DEPs including ACTBL2 (Q562R1), MBL2 (P11226), BPI (P17213), EIF3D (O15371) and CR1 (P17927) were identified as novel drug targets and predictive biomarkers for non-response to IFX. And the drug targets were confirmed in the GEO database of the microarray results from three independent cohorts of 70 human intestinal biopsies and validated in qPCR data from 17 colonic mucosal biopsies. Among them, CR1 might affect the activation of lectin pathway via complement-coated bacteria so as to play an opsonizing role in inflammation related pathways closely associated with non-responders to IFX. Conclusion: This is the first report of proteomics analysis for the identification of novel drug targets based on intestinal biopsy tissue, which is significant to hypotheses for mechanistic investigation that are responsible for non-response to IFX and the development of clinical new pharmaceutical drugs.